Analyzing the Brand Equity of Turkish Airlines Services: Comparing the Japanese and Turkish Perspectives - USLU, AYPAR; DURMUŞ, BERİL (ELSEVIER SCIENCE BV, 2013)
The main objective of this study is to empirically test a conceptual model of costumer brand equity. This study attempts to verify the determinants of brand equity of services based on consumers' perception of Turkish Airlines services. The conceptual framework of this study is based on customer-based brand equity, which includes brand loyalty, awareness, associations, perceived quality and other proprietary. This study attempts to evaluate the customer brand equity of Turkish Airline services in Turkey and Japan. 400 respondents were randomly selected and were asked their views through a structured questionnaire. This paper utilizes survey data obtained from 200 Turkish consumers who are living in Turkey and 200 Japanese consumers who are living in Japan. The findings suggest that when customers get attached emotionally to a brand (brand feeling) they go on to create strong associations with the brand. The quality of the services of a brand, its credibility, and its presence in the choice set of customers also lead to customers' strong associations with a brand. This study is one of the few researches conducted in comparing the Japanese and Turkish literature that explores thoroughly the purchasing behaviors of cross cultures in Turkish and Japanese consumers.
Keywords: Brand Equity; Turkish Airlines Services; Japanese and Turkish Perspectives